Arquitectos españoles exiliados en México - Cueto Ruiz-Funes, Juan Ignacio del (Pùblica memoria, 2014)
This book rescues the work and history of the architects who were exiled in Mexico as a result of the Republican defeat in the Spanish Civil War. The work recounts the Republican diaspora that led to the exile of fifty Spanish architects. Mexico received the largest contingent of Spanish architects in exile: a total of twenty-five.